Experimental investigation and modeling on the supersaturated total dissolved gas (TDG) dissipation in aeration - Yuanbo Yao; Huixia Yang; Yunyun Wang (Water Science and Technology, 2023)
Supersaturated total dissolved gas (TDG) generation in rivers poses great harm to aquatic organisms. In this paper, 30 groups of supersaturated TDG dissipation experiments with aeration were carried out. These results showed that aeration actively promoted the dissipation of supersaturated TDG. The aeration rate decreased by 34.94% from 1.0 m3/h to 5.0 m3/h, the reduced proportion of aeration aperture was 35.51% from 215 mm to 260 mm, whereas the aeration depth increased by 16.93% from 0.4 m to 1.2 m for the TDG dissipation time required, resulting in corresponding the variation of TDG dissipation coefficients were 86.26%, 23.74% and -5.39%, respectively. In general, the effect on TDG dissipation is that the aeration rate is the largest, followed by the aeration aperture, and the aeration depth is the smallest. A quantitative relationship was established between TDG dissipation coefficient and aeration conditions, and followed a power function, while the aeration depth inhibited its dissipation. Moreover, what matters was that a numerical model was presented for predicting the TDG dissipation in Eulerian-Eulerian. When the parameter was β = 10.52, the error between the original experimental data and the simulated of a multiphase TDG dissipation model was 0.2%. The study provides essential scientific data for mitigating the harms of supersaturated TDG. HIGHLIGHTS The effect of aeration on supersaturated TDG is analysed.; The TDG dissipation coefficient and aeration conditions are established.; When the critical TDG source treatment sensitivity parameter β = 10.52, the error between the actual supersaturated TDG dissipation process and the TDG dissipation model is 0.2%, and the experimental data and simulation values are similar.;